EKSISTENSI PEREMPUAN DALAM KELUARGA (Kajian Peran Perempuan sebagai Jantung Pendidikan Anak) - Dian Lestari (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
This paper discusses about the role of women in the family, which is different from the man, named as daughter, wife and mother. By nature, a woman is given the privilege to pregnancy, childbirth and lactation, thus automatically a woman (mother) has a closeness with children who are born. It allows a woman to be the heart of education for children in developing children's character into a superior generation. The existence of women as educators and forming the character of early childhood, making women more privileged position compared with men.